Pan-Genome Analysis Links the Hereditary Variation of Leptospirillum ferriphilum With Its Evolutionary Adaptation - Zhang, Xian; Liu, Xueduan; Yang, Fei; Chen, Lv (Frontiers in Microbiology, 2018)
Niche adaptation has long been recognized to drive intra-species differentiation and speciation, yet knowledge about its relatedness with hereditary variation of microbial genomes is relatively limited. Using Leptospirillum ferriphilum species as a case study, we present a detailed analysis of genomic features of five recognized strains. Genome-to-genome distance calculation preliminarily determined the roles of spatial distance and environmental heterogeneity that potentially contribute to intra-species variation within L. ferriphilum species at the genome level. Mathematical models were further constructed to extrapolate the expansion of L. ferriphilum genomes (an ‘open’ pan-genome), indicating the emergence of novel genes with new sequenced genomes. The identification of diverse mobile genetic elements (such as transposases, integrases, and phage-associated genes) revealed the prevalence of horizontal gene transfer events, which is an important evolutionary mechanism that provides avenues for the recruitment of novel functionalities and further for the genetic divergence of microbial genomes. Comprehensive analysis also demonstrated that the genome reduction by gene loss in a broad sense might contribute to the observed diversiﬁcation. We thus inferred a plausible explanation to address this observation: the community-dependent adaptation that potentially economizes the limiting resources of the entire community. Now that the introduction of new genes is accompanied by a parallel abandonment of some other ones, our results provide snapshots on the biological fitness cost of environmental adaptation within the L. ferriphilum genomes. In short, our genome-wide analyses bridge the relation between genetic variation of L. ferriphilum with its evolutionary adaptation.